2020
DOI: 10.3390/toxins12030142
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Effect of Satureja montana and Origanum virens Essential Oils on Aspergillus flavus Growth and Aflatoxin Production at Different Water Activities

Abstract: Aflatoxin contamination of foodstuffs poses a serious risk to food security, and it is essential to search for new control methods to prevent these toxins entering the food chain. Several essential oils are able to reduce the growth and mycotoxin biosynthesis of toxigenic species, although their efficiency is strongly influenced by the environmental conditions. In this work, the effectiveness of Satureja montana and Origanum virens essential oils to control Aspergillus flavus growth was evaluated under three w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…Therefore, currently there are known some chemotypes, based on the chemical composition of the essential oil analysis of S. montana [ 6 , 10 , 20 ]. Among them are chemotype with thymol and carvacrol domination [ 4 ], carvacrol [ 1 , 2 , 17 ], chemotype of linalool, p -cymene and α-terpineol [ 4 ], chemotype of linalool [ 6 , 10 ], intermediate chemotype of p -cymene/linalool [ 6 ], chemotype of p -cymene, thymol and carvacrol [ 6 ], chemotype of p -cymene and carvacrol [ 19 ], chemotype of myrcene and viridiflorol [ 6 ], chemotype of linalool, thymol and carvacrol [ 10 ], chemotype of p -cymene, linalool, thymol and carvacrol [ 3 ], chemotype of carvacrol, γ-terpinene, and p -cymene [ 20 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, currently there are known some chemotypes, based on the chemical composition of the essential oil analysis of S. montana [ 6 , 10 , 20 ]. Among them are chemotype with thymol and carvacrol domination [ 4 ], carvacrol [ 1 , 2 , 17 ], chemotype of linalool, p -cymene and α-terpineol [ 4 ], chemotype of linalool [ 6 , 10 ], intermediate chemotype of p -cymene/linalool [ 6 ], chemotype of p -cymene, thymol and carvacrol [ 6 ], chemotype of p -cymene and carvacrol [ 19 ], chemotype of myrcene and viridiflorol [ 6 ], chemotype of linalool, thymol and carvacrol [ 10 ], chemotype of p -cymene, linalool, thymol and carvacrol [ 3 ], chemotype of carvacrol, γ-terpinene, and p -cymene [ 20 ].…”
Section: Resultsmentioning
confidence: 99%
“…S. montana shows antiviral activity against several types of viruses, including human immunodeficiency virus type-1 (HIV-1) and Cucumber mosaic virus (CMV) [ 5 ]. Essential oil of S. montana significantly decreased the aflatoxin production by Aspergillus flavus [ 20 ]. Additionally, S. montana aqueous extracts did not show antibacterial activity.…”
Section: Introductionmentioning
confidence: 99%
“…Lambert), which used linear interpolation between successive OD readings. These TTD OD values were chosen because they more accurately represented the initiation of growth before the filamentous development for these fungi ( Carbó et al, 2018 ; García-Díaz et al, 2020 ).…”
Section: Methodsmentioning
confidence: 99%
“… Medina et al (2012) showed that the Bioscreen C system, which has been previously used for bacteria and yeast studies, could also be used for filamentous growth assays by subtle modifications of the liquid broth medium. This has allowed the rapid screening of the efficacy of novel compounds, the ecology of growth and mycotoxin production by mycotoxigenic spoilage fungi, and the comparison of formulations of biocontrol agents ( Medina et al, 2012 ; Aldars-García et al, 2018 ; Carbó et al, 2018 ; Debonne et al, 2020 ; García-Díaz et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…2020; García‐Díaz et al . 2020). However, there have been few new lead compounds which have been found for use in food and feed chains to reduce mould growth and mycotoxin contamination, without impacting on the organoleptic properties of the final product.…”
Section: Introductionmentioning
confidence: 99%